SURGICAL MANAGEMENT VERSUS NON-SURGICAL MANAGEMENT OF RIB FRACTURES IN CHEST TRAUMA: A SYSTEMATIC REVIEW - Atin, Fulgensius; Soritua Silalahi, Herbert; Prasetyanto, R. Dhany; Jimmy Desanto, Fridolino; Chindy Sulisty, Heriberty (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Roughly ten percent of patients who visit trauma centers are estimated to have broken ribs. From a single, isolated fracture to a flail chest, rib fractures can occur in a variety of severity. Rib fractures substantially influence the rates of morbidity and mortality. There is still debate on how to treat chest injuries. Practical use varies greatly; one such example is the uneven application of surgical stabilization.The aim: This study aims to assess the differences between surgical management and non-surgical management of rib fractures in chest trauma.Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and ScienceDirect, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done.Results: In the PubMed database, the results of our search brought up 44 articles, whereas the results of our search on ScienceDirect brought up 303 articles. The results of the search conducted by title screening yielded a total 18 articles for PubMed and 13 articles for ScienceDirect. We compiled a total of 17 papers, 12 of which came from PubMed and 5 of which came from ScienceDirect. We excluded 1 review article, 1 duplicate article, 1 non-full text article, 2 protocol study, 2 articles having ineligible subjects, and 3 articles having insufficient outcomes data. In the end, we included seven research that met the criteria.Conclusion: The outcomes of surgical and non-surgical methods for the management of rib fractures are comparable in terms of complications, length of hospital stay, and mortality.